The Effectiveness of Tourism Business through Positioning Method in Kandri Tourism Village, Gunungpati District (International Forum of Researchers and Lecturers, 2024)
This research examines the effectiveness of tourism business through positioning method in Kandri Tourism Village, Gunungpati District, Semarang City. The study analyzes tourism business development through market positioning strategies and tourist perceptions based on their experiences. The research was conducted using descriptive qualitative method with eight informants. Data was collected through interviews, observations, library research, and documentation. The findings indicate that Kandri Tourism Village's tourism business is currently effective in implementing positioning strategies in marketing and utilizing tourist perceptions based on their travel experiences. The village implements positioning through attributes (natural attractions, traditions), products (tour packages, crafts), and pricing strategies. Tourist perceptions demonstrate satisfaction with facilities, services, and unique experiences offered. This enables continuous development and innovation to compete with other tourism villages and attract repeat visitors.